In vitro antiproliferative potential of Cassia angustifolia extracts on HepG2 cells to combat liver cancer - Aasia Kalsoom; Awais Altaf; Muhammad Idrees Jilani; Huma Sattar; Tahir Maqbool; Tahir Muhammad (International Journal of Applied and Experimental Biology)
Liver cancer is a terrifying disease with limited treatment options and is responsible for global health and economic burden. Most anticancer options have severe adverse effects, including non-specific modes of action that aggravate the challenges of exploring effective, safe, and economical therapeutic sources. The current study aimed to decipher the cytotoxicity of ethanol (ECA) and n-hexane (HCA) extracts of a potential medicinal plant Cassia angustifolia on human liver cancer (HepG2) and noncancer human embryonic kidney (HEK-293) cells. Cassia angustifolia extracts were investigated first to profile phytocompounds through gas chromatography-mass spectrometry (GC-MS). Varying concentrations of C. angustifolia extract (10, 50, 100, 200, and 400 µg/mL) were evaluated for cytotoxicity through the MTT assay, cell viability assay, and morphological examination using a Floid cellular imaging station. Results of GC-MS analysis identified 45 compounds in ECA and HCA extracts, from which 10 compounds were common in both extracts. Most of them are reported to have antiproliferative activity. The ECA and HCA extracts showed potent cytotoxicities (IC50= 62 and 67 µg/mL) in HepG2 cells, while minimal effects on noncancer HEK-293T cells (IC50= 245 and 482 µg/mL) were recorded. The viability of cancer (HepG2) cells was calculated to be 98%, 79%, 45%, 30%, and 25% for ECA and 95%, 68%, 55%, 40%, and 31% for HCA extract, respectively. Significant percent viabilities on noncancer (HEK293T) cells were observed to be 95%, 90%, 88%, 76%, and 61% with ECA extract, and 97%, 95%, 88%, 75%, and 62% with HCA extract compared to those of untreated (UT) (100%) and DMSO (100%) treated cells. Cisplatin (positive control) exhibited ˂40% and ˂38% viabilities of cancer and normal cells, respectively. Morphological examination revealed that proliferation was reduced at 100, 200, and 400 μg/mL of the ECA extract and 200 and 400 μg/mL of the HCA extract on HepG2 cells. The HEK-293T cells did not show a noticeable decrease in viability by both extracts. In conclusion, C. angustifolia extracts showed considerable anticancer activity due to bioactive phytocompounds and were comparable to cisplatin (an FDA-approved drug). After further isolation and validation, identified phytocompounds can be available as safer anticancer candidates against liver cancer.